Chemical composition and antibacterial activity of essential oils from three aromatic plants of the Zingiberaceae family in Malaysia - Baharudin, Mohd. Khairul; Abd Hamid, Shafida; Darnis, Deny Susanti (Penerbit Universiti Sains Malaysia, 2015)
The essential oils of Boesenbergia rotunda (Temu Kunci), Curcuma mangga (Temu Pauh) and Kaempferia galanga (Cekur) were extracted using steam distillation, and the main constituents of the essential oils were analysed using gas chromatography-mass spectrometry (GC-MS). More than 10 constituents were identified in each essential oil. The main compounds in B. rotunda were nerol (39.6%) and L-camphor (36.0%), whereas ethyl-(E)-3-(4-methoxyphenyl)prop-2-enoate (57.2%) and ethyl cinnamate (39.1%) were identified in K. galanga. C. mangga contained mainly L-beta-pinene (95.6%). Antibacterial activity was assessed using the disc diffusion method and the minimum inhibitory concentration (MIC) was determined. The most active essential oil for all selected Gram-positive (Staphylococcus aureus and Bacillus cereus) and Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli) was B. rotunda (inhibition zone of 10.3–16.0 mm), followed by C. mangga (inhibition zone of 7.33–12.3 mm). The essential oil extracted from K. galanga exhibited no antibacterial activity against any of the bacteria tested. B. rotunda showed higher antibacterial activity than C. manga, with MIC values of 1.3 × 10–2 μl ml–1 (S. aureus), 2.6 × 10–2 μl ml–1 (P. aeruginosa and E. coli) and 0.66 × 10–2 μl ml–1 (B. cereus) compared to MIC values of 2.6 × 10–2 μl ml–1 (S. aureus and B. cereus) and 5.3 × 10–2 μl ml–1 (P. aeruginosa and E. coli) for C. mangga.